2018
DOI: 10.1177/1749602018763566
|View full text |Cite|
|
Sign up to set email alerts
|

Small is beautiful? The salience of scale and power to three European cultures of TV production

Abstract: As television production becomes increasingly global, television studies must advance its understanding of how the global and the local intersect and impact upon the cultures of production. Drawing on original comparative research of three small European nations – Denmark, Ireland and Wales – this article offers empirical insights into the distinct challenges and opportunities for non-Anglophone producers and public service broadcasters (PSBs). The concept of small nations is employed critically to reveal how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
2
10
0
1
Order By: Relevance
“…This is only possible due to the size and scale of the market. Scale represents a core factor that explains the emergence of this production culture, a conclusion that goes in line with recent studies focusing on other European markets (McElroy, Nielsen, & Noonan, 2018). The research showed the actors are aware that the small size of the market was a positive factor impelling the emergence of the local production culture, but they are also aware that its future sustainability is highly dependent on its ability to reach new international markets.…”
Section: Discussionsupporting
confidence: 84%
“…This is only possible due to the size and scale of the market. Scale represents a core factor that explains the emergence of this production culture, a conclusion that goes in line with recent studies focusing on other European markets (McElroy, Nielsen, & Noonan, 2018). The research showed the actors are aware that the small size of the market was a positive factor impelling the emergence of the local production culture, but they are also aware that its future sustainability is highly dependent on its ability to reach new international markets.…”
Section: Discussionsupporting
confidence: 84%
“…So for the interviewed personnel, ‘evolution’ was synonymous with massification in the sense of doing the same on a much greater scale resorting to ‘industrialised’ processes. The discourse that associates the consolidation of the local culture with issues of scale is in line with recent studies focusing on other European markets (McElroy et al, 2018), where gaining dimensions in terms of volume was also considered crucial for the consolidation of a constant flow of production. If we frame these results with the fact that most of the people interviewed had a positive attitude towards the genre and the production culture it entails, we conclude that the sample depicts high levels of self-awareness, similar to those verified for other creative industries in much larger markets such as the United States (Caldwell, 2008: 34).…”
Section: So Proud Of Themselves: the People Who Produce Telenovelassupporting
confidence: 69%
“…The article primarily focuses on Flemish drama, although broader discussions on canned export of Walloon (French-speaking Belgian) drama are also included in the paper for increased context, but not analysed in-depth, as the two Belgian markets are quite different. As such, this study both fits within a growing case study-based research on small television markets, 9 as well as recent literature strands within media economics focusing primarily on the sustainability of television markets. 10 2 E x p o r t i n g T e l e v i s i o n C o n t e n t i n S m a l l M e d i a M a r k e t s…”
Section: Introductionmentioning
confidence: 78%